Native language interference in learning english as a foreign language: an analysis of written material produced by spanish speaking students in senior high school classes - Velásquez, Teresa (2010)
Language acquisition seems to be a challenging task not only for learners but also for teachers, and even for people who seem to be very proficient in the language. Though most of the time these people are used to interacting with other English speakers, most of them face the fact that in spite of their fluency, they may use words taken from their mother tongues so as to compensate their lack of knowledge. They may do this mostly to avoid interrupting the message they are trying to convey because they may not know the proper word or structure to employ, or they may even get confused due to the similarity of words implied in the conversation. People may see this interference as a lack of knowledge of the language, but through the following work, it will be shown that different studies on the field have detected that no matter how knowledgeable they are in it, they will always have these gaps that may affect their communicative task.